Pengaruh Electronic Word of Mouth dan Atribut Produk Agrowisata terhadap Minat dan Keputusan Berkunjung ke The Blooms Garden di Kabupaten Tabanan - UMBARI, IDA AYU MILANI; ANTARA, MADE; WIJAYANTI, PUTU UDAYANI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
The Influence of Electronic Word of Mouth and Agrotourism Product Attribute on Visiting Intention and Visiting Decision to The Blooms Garden in Tabanan Regency. Electronic word of mouth and agrotourism product attribute are some factors that can influence tourist’s visiting intention and visiting decision. This study aims to 1) Analyze the influence of electronic word of mouth on visiting intention 2) Analyze the influence of electronic word of mouth on visiting decision 3) Analyze the influence of agrotourism product attribute on visiting intention 4) Analyze the influence of agrotourism product attribute on visiting decision 5) Analyze the influence of visit intention on visiting decision. Data collection method used are interviews, documentation, and literature studies. The research instrument in this study used a questionnaire. Data analysis used are descriptive analysis and SEM-PLS. The result of this study shows that electronic word of mouth has a positive and significant influence on visiting intention, electronic word of mouth has a positive and significant influence on visiting decision, agrotourism product attribute has a positive and significant influence on visiting intention, agrotourism product attribute has a positive and significant influence on visiting decision, and visiting intention has a positive and significant influence on visiting decision. The suggestion in this study is that the management of The Blooms Garden should increase the quality of content and information on social media and always maintain the facilities and tourist atrraction to increase visiting intention and tourist’s visiting decision.